TERORISME DALAM BUKU 21 LESSONS HARARI: SUATU TINJAUAN DARI PERSPEKTIF MEDIA MASSA - Sri Hadijah Arnus; Hafied Cangara; Hasrullah Hasrullah (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2021)
The concept of terrorism according to Youval Noah Harari in his book 21 Lessons says that to reduce acts of terrorism is to not commit hysteria in the mass media. Therefore, the author's question appears to further examine whether there is a mutually beneficial relationship between terrorism and the mass media. How should the mass media, government, and society behave in the face of an act of terrorism? This article uses the library study method. Based on the results of the study found that there is indeed a symbiosis between terrorism and mass media. Acts of terrorism in the mass media have news value and certainly affect the ratings of programs and media. However, it is explained that the media must still hold the principle of social responsibility that provides the best information for the audience or society. On the other hand, the government should not panic in responding to acts of terrorism. The government must establish a strategy so that all terrorism-related information can be properly controlled and not cause fear in the community.